Comparative analysis of wastewater treatment biotechnologies for small towns - Швед, Олекса Мирославович; Червецова, Вероніка Генадіївна; Петріна, Романа Омелянівна; Новіков, Володимир Павлович (Technology audit and production reserves, 2015)
A proper wastewater management is essential for sustainable development of any society. However, nowadays, Ukraine faced a huge problem with sewage treatment in small towns, which is inherited from the communist regime. The biotechnology methods of wastewater treatment are reviewed in this article in order to find an optimal solution for this problem. Two types of wastewater treatment biotechnologies can be applied to the scale of small town (capacity from 100 to 10 000 m3 of wastewaterper day): high-tech and nature-like systems. The next treatment systems were analyzed: aeration tanks, sequencing batch reactors (SBR), membrane bioreactors (MBR), oxidation ditches, trickling filters (TF), rotating biological contactors (RBC), waste stabilization ponds, aerated ponds (lagoons), and constructed wetlands. The principal schemes of selected systems were provided and feasibility analysis was performed. In conclusion, constructed wetlands were identified as the most sustainable option for treatment of wastewater of small towns with a population from 500 to 50 000 inhabitants, considering climate and economic conditions of Ukraine.